Structure-guided identification of a potential inhibitor targeting the VacA toxin of Helicobacter pylori - Farzana Akter; Md. Nur Islam; Md. Easin Mia; Md. Adnan Munim; Md. Murad Hossain (PLoS ONE, 2026)
Various human diseases including gastric inflammation, ulcers, stomach malignancies, and even coronary heart disease are significantly influenced by the infection of the gram-negative bacterium Helicobacter pylori. While antibiotics are commonly used to treat H. pylori infection, their effectiveness is compromised by the development of antibiotic resistance. Therefore, the development of novel therapeutics against this pathogen is imperative. The virulence factor “vacuolating cytotoxin autotransporter (VacA)” was annotated from H. pylori genome by using the RAST server. All strains of H. pylori contain VacA toxin. Phyre2 and SWISS-MODEL servers were used for modeling and evaluating the structure of the active site containing p55 domain of VacA toxin (PDB: 2QV3) which shows the Ramachandran plot (98.68%), MolProbity Score (1.32), Bad Bonds (0), and Clash Score (5.78) of the refined model of VacA toxin. Autodock Vina was used to dock 3000 ligand molecules obtained from the ZINC15 database which identified only 178 ligands bind to VacA’s active site. Molecular docking and ADMET studies predicted ZINC4004291 ((3As,4R,9bS)-4-pyridin-4-yl-8-(trifluoromethyl)-3a,4,5,9b-tetrahydro-3H-cyclopenta[c]quinolone) as the best inhibitor of VacA toxin based on its strong binding affinity (−6.9 kcal/mol) and low toxicity. Molecular dynamics simulation indicated favourable levels of RMSD, RMSF, Rg, SASA and Hbonds exploring the stable dynamics of the docking complex between the p55 domain of VacA toxin and ZINC4004291 ligand. Moreover, principal component analysis and Gibbs free energy landscape studies indicate the favourable thermodynamic stability of the complex during 100 ns simulation period. Thus, the ligand ZINC4004291 is a computationally identified in silico hit for a possible drug to treat H. pylori infection, while additional experimental validation required.